Utilization of Carrageenan in butter cream cake icing - Magsino, Maria Pamela Arceta; Dumelod, Benelyn Domingo (1997)
Based on a simple formulation of buttercream cake icing, an experimental formulation was developed with carrageenan incorporated in it. Six formulation of buttercream cake icing with varying levels of lambda carrageenan incorporation were prepared and subjected to sensory evaluation to determine the optimum amount of carrageenan applicable to the product. Results showed that the product with 0.90% level of carrageenan incorporation was most acceptable. The rating given to it was 7.0 which correspond to "like moderately." Three two hundred-gram production runs of the buttercream cake icing with carrageenan were done and the products were subjected to sensory evaluation to test for significant differences due to production trial. The absence of significant difference between the three production runs proved that the formulation and process were standardized. Samples of control and experimental buttercream cake icing were analyzed for moisture, crude fat, crude protein, total available carbohydrate, total dietary fiber, ash, pH, soluble solids and microbial content. Cost analysis of the buttercream cake icing with and without carrageenan was also done. Results of the analysis showed the following trends; an increase in the total dietary fiber and ash contents of the experimental cake icing as compared to the control cake icing; and a decrease in the moisture and total available carbohydrate contents of the experimental cake icing as compared to the control cake icing. The biggest increase, however, was observed in the dietary fiber content o the experimental cake icing. From the original 0.0795%, it increased by thirtyone-fold to 2.2139%. One hundred grams of the control product cost P6.77, and one hundred grams the experimental product costs P7.66. Price reduction is expected as the scale of production is increased.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Carrageenan